Globalisasi dalam Film Indonesia: Interpretasi Budaya dalam Film Naga Bonar dan Naga Bonar Jadi 2 - Cindenia Puspasari; Ade Suryani; Ratu Laura (CoverAge: Journal of Strategic Communication, 2017)
Globalization in movies has influenced in developing countries such as Indonesia, mainly in the cultural aspect. The global culture presented through movie has brought changes to the local culture. The aim of this article is to illustrate the impact of globalization in Indonesian movies in terms of culture. The two of movies will be interpretation are Nagabonar and Nagabonar Jadi 2, which are become the unit of analysis in this article. Thus, this article will compare the culture described in each movie, and focus on the interpretation of elements of cultural objects and culture is not an object.